On the Finite Differences Used in Reacting Flow Simulations (Communications in Computational Physics, 2018)
There exist many spatial discretization schemes that are well able to provideaccurate and stable approximations for isothermal turbulent flows. Comparatively littleanalysis has been made of the performance of these schemes in the presence oftemperature gradients driven by combustion. In this paper, the effects of temperaturegradients on numerical stability are explored. A surprising result is that temperaturegradients in the flow have a tendency to impinge on left half plane (LHP) stability of thespatial discretization scheme. Reasons for this tendency are explored and two remediesare proposed: one based on the particular class of finite difference schemes, andone based on an alternative method of boundary condition specification.